Effect of Dietary 1, 25-Dihydroxycholecalciferol Concentration on Growth Performance and Bone Characteristics of Japanese Quail Fed Diet Deficient in Calcium and Phosphorus - Sheikhlar, A.; Navid, S. (Pakistan Journal of Nutrition, 2009)
An investigation was carried out to assay the concentration of dietary 1, 25-dihydroxycholecalciferol [1, 25(OH)2D3] on growth parameters and bone characteristics includes bone ash, Tibial Dyschondroplasia (TD) incidence and plasma minerals in broiler quails. Diets comprised control diet (diet 1) with sub optimal levels of calcium (0.71%) and total phosphorus (0.37%) and diets 2, 3, 4 and 5 that contained control diet supplemented with 2.5, 4.5, 6.5 or 8.5 μg/Kg 1,25(OH)2D3. Dietary treatments had no effect (p>0.05) on the live weight gain and feed conversion ratio. Bone ash was increased significantly (p<0.05) by 6.5 μg/Kg 1, 25(OH)2D3 at 3 wk of age. Treatments effects were shown (p<0.05) on calcium of bone but there was no influence on bone’s phosphorus. The incidence and severity of TD were reduced pronouncedly (p<0.05) by 6.5 μg/Kg 1, 25(OH)2D3 at 3 wk of age. Plasma calcium improved significantly (p<0.05) however; plasma phosphorus did not show any differences (p>0.05) among experimental treatments. In conclusion, dietary level of 6.5 μg/Kg 1, 25(OH)2D3 showed positive effect on the reduction of TD in broiler quails at 3 wk of age.